2012
DOI: 10.1097/shk.0b013e3182429b38
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Technical Considerations Regarding the Removal of Bacteriotoxins in Sepsis With Emphasis on Toxic Shock Syndrome Toxin 1

Abstract: Severe sepsis is characterized by rapid development of multiple organ failure associated with high mortality. Bacterial toxin release triggers a sequence of events that activates intracellular pathways to produce inflammatory mediators and nitric oxide. There have been numerous attempts to interrupt this devastating cascade by removing toxins, removing or inhibiting mediators, and by blocking receptors of mediators. This review considers toxin properties with a strong focus on toxic shock syndrome toxin 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Sepsis is a highly lethal condition characterized by systemic inflammation, resulting from uncontrolled host immune responses to a serious infection 5 . The strong activation of whole-body inflammation is essential for preventing against the invading pathogens, but may cause detrimental consequences such as multiple-organ failure 52 , 53 . As the major members of the innate immune system, neutrophils, and macrophages recognize the microbial components such as the bacterial LPS and participate in the clearance of microbes during sepsis 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is a highly lethal condition characterized by systemic inflammation, resulting from uncontrolled host immune responses to a serious infection 5 . The strong activation of whole-body inflammation is essential for preventing against the invading pathogens, but may cause detrimental consequences such as multiple-organ failure 52 , 53 . As the major members of the innate immune system, neutrophils, and macrophages recognize the microbial components such as the bacterial LPS and participate in the clearance of microbes during sepsis 54 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that ET's inhibition of arterial contractile function might be mediated in part by release of an endothelial derived relaxant factor (EDRF). Nitric oxide (NO) is a potent EDRF, which has been associated with the pathogenic effects of several bacterial toxins (4,6,37). Therefore, using both an ex vivo rat aortic ring model and an in vivo rat model, in combination with three nitric oxide synthase (NOS) inhibitors with the potential to inhibit one or more of the three NOS isoforms [endothelial (eNOS), neuronal (nNOS), and inducible (iNOS)], we tested the hypothesis that NO production contributes to ET's hypotensive and lethal effects.…”
mentioning
confidence: 99%